One Anastomosis Gastric Bypass Surgery: Consequences Over Diabetic Parameters (Bangladesh Journal of Medical Science, 2024)
Introduction: Excessive weight gain in individuals leads to various metabolic disorders, such as diabetes mellitus, contributing to a further increase in body mass index (BMI). Thus, the patient enters a vicious cycle that leads to irreversible health damage. Bariatric surgery has displayed positive outcomes of weight loss with the return of BMI towards normal, which may reduce blood glucose levels to near normal. The remission of diabetes mellitus may be attributed to the reduction in inflammation, improvement of insulin resistance, lowering of peptide YY, and overall improved metabolic state of the body.Methods: One fifty patients, both female and male, in the age group of 20-60 years with grade II and grade III obesity having mean BMI of 45.63±6.54 (male) and 41.81± 5.93kg/m2 (female) were randomly selected for this study. Hemoglobin, Fasting Blood sugar (FBS), 2 hours postprandial blood sugar (PP2BS). Hemoglobin A1c (HbA1c) serum insulin was assessed at the visit, marked as a baseline, then again at the visit 3 months, and finally at the visit by the patient 6 months after bariatric surgery.Results: Hemoglobin level increased significantly from baseline at the 3rd-month post-surgery visit. FBS increased substantially from baseline at the 3rd-month postsurgery visit, which decreased considerably at the 6th-month visit following surgery. HbA1c showed a significant decrease in level from baseline following surgery.Conclusion: Improvement in BMI following bariatric surgery may have a positive impact on blood glucose levels in diabetic patients who may hope to see better management of their condition and may enjoy a better quality of life.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 29-38